Impact of transmission dynamics on the cost-effectiveness of rotavirus vaccination - Shim, Eunha; Galvani, Alison P. (Vaccine, 2009)
The objective of this study is to estimate the cost-effectiveness of mass vaccination of US infants with the recently available rotavirus vaccine, RotaTeq. We developed a dynamic transmission model of rotavirus to incorporate herd immunity into cost-effectiveness analysis. Our study indicates that a rotavirus vaccination program would prevent about 90% of rotavirus incidence, mortality, hospitalization and emergency department visits annually. We conclude that a universal rotavirus vaccine program in the US would cost $77.30 per case averted from the health care and give a net saving of $80.75 per case averted from the societal perspectives, respectively. The cost per QALY gained was found to be $104,610 when we considered child with one caregiver, making the rotavirus vaccination program a cost-effective intervention.